2017
DOI: 10.1503/cmaj.170017
|View full text |Cite
|
Sign up to set email alerts
|

Oral morphine versus ibuprofen administered at home for postoperative orthopedic pain in children: a randomized controlled trial

Abstract: BACKGROUND:Oral morphine for postoperative pain after minor pediatric surgery, while increasingly popular, is not supported by evidence. We evaluated whether oral morphine was superior to ibuprofen for at-home management of children's postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 54 publications
3
33
0
3
Order By: Relevance
“…The clinical study observed a significant reduction of fentanyl utilization, without risk of complications, including post-surgery bleeding. • Children aged 1-10 years who needed tonsillectomy and/or adenoidectomy received ibuprofen or the association of paracetamol/ morphine (29). The results of the study showed similar analgesic efficacy with the advantage of no morphine induced respiratory depresa, in case of ibuprofen use.…”
Section: The Safety Profile Of Ibuprofen Administred To Childrenmentioning
confidence: 89%
“…The clinical study observed a significant reduction of fentanyl utilization, without risk of complications, including post-surgery bleeding. • Children aged 1-10 years who needed tonsillectomy and/or adenoidectomy received ibuprofen or the association of paracetamol/ morphine (29). The results of the study showed similar analgesic efficacy with the advantage of no morphine induced respiratory depresa, in case of ibuprofen use.…”
Section: The Safety Profile Of Ibuprofen Administred To Childrenmentioning
confidence: 89%
“…There have been 3 recent trials studying oral morphine therapy for musculoskeletal injury. [24][25][26] In 2 trials, the investigators compared oral morphine therapy to ibuprofen, alone and in combination, and found no significant difference in efficacy. 24,25 In addition, all 3 trials showed significantly more adverse effects in the morphine group than in the ibuprofen group.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] In 2 trials, the investigators compared oral morphine therapy to ibuprofen, alone and in combination, and found no significant difference in efficacy. 24,25 In addition, all 3 trials showed significantly more adverse effects in the morphine group than in the ibuprofen group. In contrast, physicians in our study reported that orally administered morphine was their preferred opioid for moderate and severe pain at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, findings from this study are only applicable to the emergency department environment. For example, we do not know whether using ibuprofen+morphine at home improves pain compared with ibuprofen only (although there are data to suggest it does not4). Second, participants were chosen using very selective criteria.…”
Section: Commentarymentioning
confidence: 99%